Rapid Diagnosis of Malaria by Antigen Detection (Bangladesh Journal of Medical Microbiology, 2009)
The study was conducted to evaluate the sensitivity and specificity of Immunochromatographic test (ICT) for antigen, using microscopy as the "gold standard" method for diagnosis of malaria. A total of 98 clinically suspected malaria patients and another 30 age and sex-matched healthy controls were included in this study. Thick and thin films were also prepared and examined under microscope as well as Immunochromatographic test (ICT) was performed for malaria antigen. Sensitivity and specificity of ICT for antigen were 93.22% and 94.87% respectively. Keywords: Detection of malaria antigen, Immunochromatographic test   doi: 10.3329/bjmm.v3i1.2965 Bangladesh J Med Microbiol 2009; 03 (01): 14-16